#### Answer

Net change: -6
Average rate of change: -3

#### Work Step by Step

We find the net change from $x=1$ to $x=3$:
$f(3)-f(1)=-1-5=-6$
Next we find the average rate of change for this interval:
$\frac{f(3)-f(1)}{3-1}=\frac{-6}{2}=-3$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

Net change: -6
Average rate of change: -3

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.